PENINGKATAN KESEJAHTERAAN SOSIAL KOMUNITAS ADAT TERPENCIL BERBASIS KEARIFAN LOKAL - Bambang Rustanto (Politeknik Kesejahteraan Sosial, 2007)
Sosial welfare always linked with economy growth but actually the economy growth has contributed to natural resources damaged. Indigenous people (KAT) which stay in these circumstances often get impact from damaged of natural resources. Empowerment of indigenous people (KAT) must pay attention to the relation between human with nature as eco-system. So natural resources management for indigenous people (KAT) life must be adequate proper with the natural power support.Key word : social welfare, empowerment of indigenous people.